THE VALUE CHAIN OF FISH FOR FLOATING CAGES AND POND TECHNIQUES IN BAGHDAD PROVINCE - & et al., AL- Flujy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The fish sector is considered an important component of the economies of many countries in the world including Arab countries . This work is considered as the first attempt to study value chain for fish in Iraq. The objective of this study is to identify the main problems and constraints facing different channels or links the value chain of fish, and to analyse revenue, production costs, and to calculate some quantitative indicators like value added . The results showed that average value added of the different links are amount: 22.13dinars/kg, 1007.7 dinar/kg, 242.9 dinar/kg and 1023.5 dinars/kg from each links hatcheries, producers, wholesalers and retailers , the results also showed that the share of different links from value chain for average value additionrs as follows : 0.96% for hatcheries link , 43.8% for producer link , 10.6% for wholesalers link and 44.6% for retailers link. While cages producers added 68.5% from average value added it is amount 2796. 9 dinar/ kg on level techniques of floating cages . The study also identifis the main challenges and problems facing each link in chain value and forward the suitable solution and recommendation for government Authorities and private sector in order to increase the efficiency of fish in Iraq .